2.57¶
; Extend the differentiation program to handle sums and products of arbitrary ; numbers of (two or more) terms. Then the last example above could be expressed ; as ; (deriv '(* x y (+ x 3)) 'x) ; Try to do this by changing only the representation for sums and products, ; without changing the deriv procedure at all. For example, the addend of a sum ; would be the first term, and the augend would be the sum of the rest of the terms. ; New definitions for `augend` and `multiplcand` are, ; ==================================================== (define (augend s) (if (null? (cdddr s)) (caddr s) (make-sum (caddr s) (cadddr s)))) (define (multiplicand p) (if (null? (cdddr p)) (caddr p) (make-product (caddr p) (cadddr p)))) ; ==================================================== ; Testing (define (variable? x) (symbol? x)) (define (same-variable? v1 v2) (and (variable? v1) (variable? v2) (eq? v1 v2))) (define (=number? exp num) (and (number? exp) (= exp num))) (define (sum? x) (and (pair? x) (eq? (car x) '+))) (define (addend s) (cadr s)) (define (make-sum a1 a2) (cond ((=number? a1 0) a2) ((=number? a2 0) a1) ((and (number? a1) (number? a2)) (+ a1 a2)) (else (list '+ a1 a2)))) (define (product? x) (and (pair? x) (eq? (car x) '*))) (define (multiplier p) (cadr p)) (define (make-product m1 m2) (cond ((or (=number? m1 0) (=number? m2 0)) 0) ((=number? m1 1) m2) ((=number? m2 1) m1) ((and (number? m1) (number? m2)) (* m1 m2)) (else (list '* m1 m2)))) (define (deriv exp var) (cond ((number? exp) 0) ((variable? exp) (if (same-variable? exp var) 1 0)) ((sum? exp) (make-sum (deriv (addend exp) var) (deriv (augend exp) var))) ((product? exp) (make-sum (make-product (multiplier exp) (deriv (multiplicand exp) var)) (make-product (deriv (multiplier exp) var) (multiplicand exp)))) (else (error "unknown expression type: DERIV" exp)))) (deriv '(* x y (+ x 3)) 'x) ; (+ (* x y) (* y (+ x 3))) (deriv '(* x y (+ x 3 y)) 'x) ; (+ (* x y) (* y (+ x 3 y)))